1999
DOI: 10.1161/01.cir.99.2.299
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Activated Factor XIII to Fibrinolytic Resistance in Experimental Pulmonary Embolism

Abstract: Background —The resistance of thrombi to fibrinolysis induced by plasminogen activators remains a major impediment to the successful treatment of thrombotic diseases. This study examines the contribution of activated factor XIII (factor XIIIa) to fibrinolytic resistance in experimental pulmonary embolism. Methods and Results —The fibrinolytic effects of specific inhibitors of factor XIIIa–mediated fibrin-fibrin cross-linking and α2-antiplasmin–fibrin cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 46 publications
1
59
2
1
Order By: Relevance
“…To examine this possibility, we used a small ␣ 2 AP peptide (␣ 2 AP 13-24 , Ϸ1600 Da), which should readily permeate the developing thrombus. We and others have verified that this peptide 5 or related peptides 16,17 can compete with crosslinking of ␣ 2 AP to fibrin when added during clotting. This peptide was biotinylated at lysine 24 to permit detection.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…To examine this possibility, we used a small ␣ 2 AP peptide (␣ 2 AP 13-24 , Ϸ1600 Da), which should readily permeate the developing thrombus. We and others have verified that this peptide 5 or related peptides 16,17 can compete with crosslinking of ␣ 2 AP to fibrin when added during clotting. This peptide was biotinylated at lysine 24 to permit detection.…”
Section: Resultsmentioning
confidence: 64%
“…5 We found that the catalytic ability of FXIIIa to cross-link its physiological substrate (␣ 2 AP, 70 000 Da) into fibrin clots declined in an exponential fashion, with a half-life of 19 minutes. Similar half-lives for FXIIIa-mediated cross-linking were also found in much smaller substrates, such as ␣ 2 AP 13-24 (1600 Da), 21 minutes, and pentylamine-biotin (330 Da), 26 minutes.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations